Are there clinical phenotypes of homozygous sickle cell disease? - Alexander, N; Higgs, D; Dover, G; Serjeant, G (2004)
The distribution of clinical features was examined in subjects with homozygous sickle cell (SS) disease in the Jamaican Cohort Study to determine whether there is evidence of distinct clustering of symptoms or clinical phenotypes. A twofold model yielded groups that could be interpreted as painful crisis or leg ulcer phenotypes and 78% of patients were classified with 95% confidence into one of these. The painful crisis phenotype also manifested higher frequencies of dactylitis, meningitis/septicaemia, acute chest syndrome and stroke. Attempts to define a three-group model were less convincing although 43% of patients could be allocated with 95% confidence. The three-group model essentially divided subjects with the leg ulcer phenotype into subgroups with higher and lower frequencies of painful crisis, dactylitis, meningitis/septicaemia and acute chest syndrome. In the three-group model, the painful crisis phenotype had lower total haemoglobin, fetal haemoglobin, mean cell volume and higher reticulocytes but there was no apparent influence of alpha thalassaemia or beta globin haplotype. Both environmental and genetic factors are likely to contribute to most manifestations of SS disease and the evidence for different clinical phenotypes suggests that a search for associated genetic polymorphisms may provide insights into the mechanisms of clinical variability in SS disease.